2018
DOI: 10.1039/c7ta10898b
|View full text |Cite
|
Sign up to set email alerts
|

Tough, adhesive and self-healing conductive 3D network hydrogel of physically linked functionalized-boron nitride/clay /poly(N-isopropylacrylamide)

Abstract: A multi-functional delicate conductive nanostructure of a 3D hierarchical physically linked f-BNNS/clay/PNIPAM hydrogel has been fabricated successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 67 publications
2
67
0
Order By: Relevance
“…[48,76,[78][79][80] Polyvinylpyrrolidone (PVP) outperformed Pluronics F127 and P123, Tween 20, hexadecyltrimethylammonium bromide (CTAB), and sodium dodecylbenzenesulfonate (SDBS) for exfoliation in scCO 2 mixed solvent solutions. [48,76,[78][79][80] Polyvinylpyrrolidone (PVP) outperformed Pluronics F127 and P123, Tween 20, hexadecyltrimethylammonium bromide (CTAB), and sodium dodecylbenzenesulfonate (SDBS) for exfoliation in scCO 2 mixed solvent solutions.…”
Section: Complex Fluid Processingmentioning
confidence: 99%
“…[48,76,[78][79][80] Polyvinylpyrrolidone (PVP) outperformed Pluronics F127 and P123, Tween 20, hexadecyltrimethylammonium bromide (CTAB), and sodium dodecylbenzenesulfonate (SDBS) for exfoliation in scCO 2 mixed solvent solutions. [48,76,[78][79][80] Polyvinylpyrrolidone (PVP) outperformed Pluronics F127 and P123, Tween 20, hexadecyltrimethylammonium bromide (CTAB), and sodium dodecylbenzenesulfonate (SDBS) for exfoliation in scCO 2 mixed solvent solutions.…”
Section: Complex Fluid Processingmentioning
confidence: 99%
“…The introduction of three network structures in hydrogels increased the number of attachment points between molecules, thus significantly enhancing the mechanical strength of hydrogels . Tong et al designed physically linked gel by combining functionalized‐boron nitride nanosheets with H‐grafted nitrogen/‐OH grafted boron atoms with high toughness, adhesiveness, and automatical self‐healing abilities, while the conditions for self‐healing were harsh.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional chemical cross‐linked hydrogels, physical hydrogels (the cross‐linking structure is formed by non‐covalent bonding, such as hydrophobic association,] π–π stacking, hydrogen bonds, electrostatic interactions, and host–guest recognition) often exhibit good self‐healing performance, which has broad application prospects in industry, agriculture, biomedicine, and many other fields . However, the physical hydrogels generally suffer from their low mechanical strength, which greatly limits the development of high‐performance hydrogels .…”
Section: Introductionmentioning
confidence: 99%
“…As a physical hydrogel, HA‐gel has good self‐healing property, energy dissipation ability, and elongation, but low mechanical strength . In our previous work, we have demonstrated some general approaches to improve the strength and self‐healing ability of HA gels by combining the synergistic cross‐linking effects provided by crystalline microdomains, ionic interactions, and hydrophobic association micelles. The results showed that the formation of multiple physical cross‐linking structures is conducive to high strength and excellent self‐healing properties of the hydrogels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation